INOVASI HIJAU TRANSFORMASI LIMBAH PERTANIAN MENJADI PRODUK BERKUALITAS - Nur Inayah, Astrina; Rukmelia, Rukmelia; Salfiana, Salfiana; Nurwidah, Andi; Hasanuddin, Fenny; Haryono, Iranita; Padapi, Astrini; Reskianti, Reskianti; Rabiah, Rabiah; Nur Zahilah, Rizka (Jurnal Pengabdian Masyarakat Sabangka, 2024)
The problems that occur in the Asoka Women Farmers Group include agricultural activities, increasing product innovation capacity, resulting in a lack of access to agricultural education and training which hinders the progress of the women farmers group. The problem that occurs with domestic waste is difficulty in management. Overcoming the domestic waste problem requires a holistic approach through innovative green waste management. The aim of the implementation is to carry out mentoring activities for green innovation in the transformation of agricultural waste into quality products. The method is a method of counseling and training in making dodol from banana peels, crackers from tofu dregs and candied watermelon peels. The partners involved in this activity are the Asoka Farming Women's Group, Kelurahan Kadidi. The activity was implemented on January 13 2024. The results of this activity were an increase in knowledge which could be seen from the community's activeness in the activity. The conclusion that can be drawn from this activity is that the implementation of the activity ran smoothly in collaboration with Kadidi Village officials. Participants were very enthusiastic in taking part in the activity.